Coral-like nano-mgO, preparation process and application thereof in sugar juice clarification

CN122940190APending Publication Date: 2026-10-20GUANGXI UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611226705.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0008]针对现有技术中纳米氧化镁形貌与孔结构难以协同调控、吸附选择性不足、循环稳定性差、糖汁清净应用效果有限的缺陷,本发明提供一种珊瑚状纳米MgO、制备工艺及其在糖汁清净中的应用,通过多原料复合调控与多工艺耦合优化,制备得到分级多孔珊瑚状镧改性纳米氧化镁,兼具高比表面积、高吸附活性、高脱色选择性与高循环稳定性,可高效应用于糖汁清净工序,替代传统硫熏工艺,提升糖品安全品质

Benefits of technology

[0023]1.本发明通过螯合形貌调控与生物软模板造孔的耦合,同步实现了珊瑚状分级形貌的构建与内部介孔结构的生成,形成了“大孔传质-介孔吸附”的分级孔道体系。相较于现有技术中单一形貌调控得到的无孔珊瑚状氧化镁,本发明的分级孔道可大幅降低糖汁中大分子色素的内扩散阻力,使色素分子能够快速抵达颗粒内部的吸附位点,显著提升吸附速率;同时内部介孔大幅增加了有效吸附比表面积,提供了更多的吸附位点,显著提升了吸附容量。相较于普通颗粒状纳米氧化镁,本发明的珊瑚状分级结构避免了颗粒紧密团聚导致的内部位点失活,有效吸附位点占比大幅提升,传质效率与吸附容量实现了同步优化,能够更好地适配糖汁清净的工业应用场景,缩短吸附处理时间,提升生产效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a coral-like nano-MgO, its preparation process, and its application in sugar juice purification. Using magnesium chloride hexahydrate as the magnesium source, trisodium citrate dihydrate as a morphology modifier, sucrose as a bio-based soft template, and lanthanum chloride hexahydrate as a modifier, a sodium carbonate-urea coupled precipitation combined with solvothermal directional growth is employed. Fractional porous coral-like nano-MgO is prepared through segmented calcination and crystallization. The coral-like nano-MgO of this invention exhibits high adsorption activity and good selectivity, resulting in high decolorization efficiency and strong cycle stability when used for sugar juice purification. It can replace traditional sulfur fumigation processes, reducing sulfide residues and improving the safety and quality of sugar products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterial preparation and sugar engineering technology, specifically relating to a coral-like nano-MgO, its preparation process, and its application in sugar juice purification. Background Technology

[0002] Sugarcane sugar production is a crucial component of my country's food industry, and the quality of its products directly impacts the quality and safety of the food processing supply chain and the industry's economic benefits. In the entire sugar production process, the purification process is the core step determining the quality of the finished sugar. Its primary function is to remove various non-sucrose impurities from the sugarcane juice, including phenolic substances, melanoidins, caramel coloring, and other colored components, as well as starch, pectin, protein, amino acids, colloidal substances, and various inorganic salts. These impurities not only directly increase the color value of the finished sugar and reduce its sucrose purity, but also accelerate scale buildup in heat exchange equipment during subsequent processes such as evaporation and boiling, reducing heat transfer efficiency, increasing energy consumption and equipment maintenance costs. Furthermore, the presence of these impurities shortens the shelf life of the finished sugar, affecting its market competitiveness.

[0003] Currently, most sugar mills in China use the sulfite process as their mainstream purification process. This process generates sulfur dioxide through sulfur combustion, which is then introduced into pre-ashed sugarcane juice to complete the sulfur fumigation neutralization reaction. The newly formed calcium sulfite precipitate generated during the reaction process adsorbs and removes impurities. The sulfite process has the advantages of a short process flow and low operating costs, making it suitable for large-scale industrial production. However, with the continuous improvement of environmental protection requirements and food safety standards, its inherent defects are becoming increasingly prominent: First, the sulfur combustion process produces waste gas containing sulfides, which, if not properly treated, can easily cause air pollution, significantly increasing the environmental governance costs and compliance pressure on enterprises. Second, the sulfur fumigation process leaves sulfites in the sugar solution. Although this meets current standards, it still poses food safety control risks and is difficult to meet the demand for sulfur-free sugar products in high-end sugar-free foods, infant formula, and other fields. In addition, the adsorption capacity and selectivity of calcium sulfite precipitate are limited, and its removal effect on difficult-to-decolorize large molecular impurities such as melanoidins and polyphenols is not good. It is difficult to produce premium or refined white sugar with lower color values ​​and higher quality by relying solely on the sulfite process. The carbonation process is more effective than the sulfite process, but it has drawbacks such as high lime consumption, high filter mud production, and high treatment costs, making it difficult to promote on a large scale in the industry.

[0004] To achieve sulfur-free purification and improve sugar product quality, the industry has gradually begun research and application of magnesium-based purifying agents. Magnesium hydroxide, due to its high adsorption activity, sulfur-free residue, and environmental friendliness, has become an important research direction to replace the sulfite process. Chinese patent literature, "A Method for Using Newly Born Magnesium Hydroxide for Sugar Juice Purification" (Publication No.: CN122060937A), discloses a newly born magnesium hydroxide material and its preparation process for sugar juice purification. This invention uses NaOH and MgCl2·6H2O as raw materials to prepare a newly born magnesium hydroxide slurry. By controlling different pH and temperature, good turbidity removal and decolorization effects were achieved. However, the finished magnesium hydroxide product inevitably suffers from activity decay during storage and transportation, and the magnesium hydroxide floc structure is loose and difficult to separate, requiring supporting separation methods such as bubbling flotation or pressure filtration. Furthermore, the decolorization rate still needs further improvement to meet the application requirements of high-quality sugar products.

[0005] Nano-magnesium oxide, as a novel inorganic functional material, exhibits better chemical and thermal stability compared to magnesium hydroxide. Furthermore, its high specific surface area and abundant surface defects due to its nanoscale size endow it with excellent adsorption properties, demonstrating promising application potential in water treatment, gas adsorption, and food processing. However, nano-magnesium oxide prepared by conventional precipitation methods generally suffers from severe particle agglomeration, irregular morphology, and underdeveloped pore structure, resulting in low specific surface area and adsorption capacity and rate that fail to meet industrial application requirements. To optimize the morphology and pore structure of nano-magnesium oxide, existing technologies often employ single organic solvents or surfactants for morphology control. However, single control methods cannot simultaneously improve morphological regularity and construct hierarchical pore structures. The resulting coral-like magnesium oxide is mostly simple particle agglomerates, lacking hierarchical pore design. This leads to high diffusion resistance of macromolecular pigments in sugar juice within the particles, long adsorption equilibrium times, and low mass transfer efficiency.

[0006] Meanwhile, existing research on the modification of nano-magnesium oxide mainly focuses on the treatment of heavy metal wastewater, with limited research on the selective modification of polar pigments in syrup systems. Furthermore, techniques such as rare earth doping, morphology control, and pore structure construction are mostly used individually, lacking synergistic coupling designs. Single morphology enhancement can only increase physical adsorption sites and cannot strengthen the chemical adsorption of polar pigments such as phenols and melanoidins. Single doping modification, without high specific surface area structural support, cannot fully expose active sites, making it difficult to achieve the desired modification effect. In addition, existing preparation processes often employ single-stage direct calcination, with simultaneous rapid decomposition of the organic template and precursor, easily leading to pore collapse and particle sintering. This fails to simultaneously preserve pore structure and regulate crystal activity, resulting in poor product recycling stability and significant degradation of adsorption performance after multiple regenerations.

[0007] In summary, existing technologies cannot simultaneously achieve morphological regulation, hierarchical pore construction, surface activity modification, and structural stability enhancement of nano-magnesium oxide. The resulting products suffer from low decolorization efficiency, poor selectivity, short cycle life, and insufficient industrial adaptability in sugar juice purification applications, making it difficult to fully replace the traditional sulfite purification process. Therefore, developing a coral-like nano-magnesium oxide preparation process that combines high adsorption capacity, high decolorization selectivity, high cycle stability, and ease of industrial production is of significant practical importance for promoting the upgrading of sulfur-free purification technology in the sugar industry and improving the safety and quality of sugar products. Summary of the Invention

[0008] To address the shortcomings of existing technologies, such as difficulty in synergistically controlling the morphology and pore structure of nano-magnesium oxide, insufficient adsorption selectivity, poor cycle stability, and limited application effect in sugar juice purification, this invention provides a coral-like nano-MgO, its preparation process, and its application in sugar juice purification. Through multi-raw material composite control and multi-process coupling optimization, hierarchical porous coral-like lanthanum-modified nano-magnesium oxide is prepared, which has high specific surface area, high adsorption activity, high decolorization selectivity, and high cycle stability. It can be efficiently applied to the sugar juice purification process, replacing the traditional sulfur fumigation process and improving the safety and quality of sugar products.

[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a preparation process for coral-like nano-MgO, comprising the following steps:

[0010] (1) Preparation of precursor solution: Add magnesium chloride hexahydrate to ethylene glycol-deionized water mixed solvent and stir magnetically at room temperature until completely dissolved; add trisodium citrate dihydrate, sucrose and lanthanum chloride hexahydrate in sequence and continue stirring until a homogeneous and transparent mixed salt solution is formed.

[0011] (2) Coupled precipitation and solvothermal growth: Prepare sodium carbonate-urea composite precipitant, add it dropwise to the mixed salt solution in step (1), and continue to stir evenly after the addition is complete; then transfer it to a hydrothermal reactor lined with polytetrafluoroethylene and seal it for solvothermal treatment;

[0012] (3) Post-processing and drying: After the reaction is completed, the mixture is naturally cooled to room temperature, allowed to stand and age at room temperature, and then filtered to obtain a white precursor precipitate. The precipitate is washed alternately with deionized water and anhydrous ethanol until the filtrate is free of chloride ions. After drying at a constant temperature, the precipitate is ground to obtain the precursor powder.

[0013] (4) Segmented calcination crystallization: The precursor powder is spread evenly in the corundum boat, placed in a tube furnace, and calcined in an air atmosphere using a two-stage temperature rise program. After natural cooling in the furnace, coral-like nano-MgO is obtained.

[0014] Preferably, the volume ratio of the ethylene glycol-deionized water mixed solvent in step (1) is 3-5:1.

[0015] Preferably, in step (1), the amount of trisodium citrate dihydrate used is 3%-10% of the mass of magnesium chloride hexahydrate, and the amount of sucrose used is 5%-12% of the mass of magnesium chloride hexahydrate.

[0016] Preferably, the amount of lanthanum chloride hexahydrate used in step (1) is 0.2%-1.2% molar ratio of lanthanum to magnesium.

[0017] Preferably, in step (2), the molar ratio of sodium carbonate to urea in the composite precipitant is 0.5-1:1, the molar ratio of magnesium to carbonate in the system is 1.1-1.5:1, the temperature of the solvent heat treatment is 120-160℃, the holding time is 2-6h, and the filling degree of the reactor is controlled at 65%-75%.

[0018] Preferably, in step (3), the washed precipitate is placed in an oven and dried at 78-82℃ for 9-10 h before being ground to obtain precursor powder.

[0019] Preferably, the two-stage temperature rise calcination in step (4) is as follows: first, the temperature is raised to 250-300℃ at 1-3℃ / min and held for 1-2 hours, and then the temperature is raised to 420-480℃ at 2-4℃ / min and held for 1-3 hours.

[0020] The present invention also provides a coral-like nano-MgO, wherein the coral-like nano-MgO is assembled from nanorods to form a coral-like branched hierarchical structure, and has mesoporous hierarchical channels inside.

[0021] This invention also provides an application of coral-like nano-MgO in the purification and decolorization of sugar juice. The coral-like nano-MgO is added to the sugar juice to be purified at a mass concentration of 4-10 g / L, and adsorption and decolorization are carried out under constant temperature stirring at 30-70℃ for 20-60 min. After adsorption is completed, the purified sugar juice is obtained by solid-liquid separation.

[0022] Compared with the prior art, the technical advantages of this invention are:

[0023] 1. This invention, through the coupling of chelation morphology control and pore-forming with a biological soft template, simultaneously achieves the construction of a coral-like hierarchical morphology and the generation of internal mesoporous structures, forming a hierarchical pore system of "macropore mass transfer-mesoporous adsorption". Compared to the non-porous coral-like magnesium oxide obtained by single morphology control in the prior art, the hierarchical pores of this invention can significantly reduce the internal diffusion resistance of macromolecular pigments in sugar juice, enabling pigment molecules to quickly reach the adsorption sites inside the particles, significantly improving the adsorption rate; at the same time, the internal mesopores greatly increase the effective adsorption specific surface area, providing more adsorption sites and significantly improving the adsorption capacity. Compared to ordinary granular nano-magnesium oxide, the coral-like hierarchical structure of this invention avoids the deactivation of internal sites caused by the tight aggregation of particles, significantly increases the proportion of effective adsorption sites, and achieves simultaneous optimization of mass transfer efficiency and adsorption capacity, which can better adapt to the industrial application scenario of sugar juice purification, shorten the adsorption treatment time, and improve production efficiency.

[0024] 2. This invention employs a precipitation method that couples rapid nucleation of sodium carbonate with slow growth of urea, combined with directional crystal growth under a solvothermal environment. Compared to the traditional direct precipitation method at room temperature, this allows for precise control of the crystal nucleation and growth processes. In traditional precipitation methods, excessively high local concentrations of the precipitant can lead to disordered simultaneous nucleation and growth, resulting in products with wide particle size distribution, chaotic morphology, and poor structural stability, making them prone to structural breakage during adsorption and regeneration. The coupled precipitation process of this invention first forms a large number of uniform crystal nuclei, then achieves synchronous crystal growth through the slow release of precipitated ions from urea. The high-temperature, high-pressure environment of the solvothermal environment further promotes crystal development, resulting in products with high morphological regularity, uniform size distribution, and good crystal structure integrity. These products are less prone to structural collapse and breakage during adsorption, stirring, and high-temperature regeneration, maintaining the integrity of the hierarchical structure over a long period, thus improving the product's stability and service life from the structural perspective.

[0025] 3. This invention introduces trace amounts of rare earth lanthanum to modify nano-magnesium oxide. Through the combined effect of lattice distortion and highly dispersed lanthanum oxide on the surface, the adsorption selectivity for polar pigments such as phenols and melanoidins in sugar juice is significantly improved. Existing ordinary nano-magnesium oxide mainly relies on physical adsorption and weak hydrogen bonding of surface hydroxyl groups to adsorb pigments. It has weak attraction to highly polar and difficult-to-decolorize components, resulting in poor removal efficiency and susceptibility to competitive adsorption from other non-pigment impurities in the sugar juice. The lanthanum modification of this invention introduces a large number of coordinated unsaturated active sites and strongly polar adsorption sites onto the magnesium oxide surface. Through surface complexation and strong hydrogen bonding, it specifically adsorbs polar pigment molecules, not only improving the overall decolorization efficiency but also significantly enhancing the removal capacity for difficult-to-decolorize components. This effectively reduces the color value of the finished sugar and improves the quality grade of the sugar product. Simultaneously, trace doping does not significantly increase raw material costs and does not introduce impurities harmful to sugar quality, ensuring good food application safety.

[0026] 4. This invention employs a segmented calcination process of low-temperature template removal followed by medium-temperature crystallization. Compared to traditional single-stage direct calcination, this process allows for the orderly and sequential removal of the organic template, precursor decomposition, and crystal growth. In traditional single-stage calcination, organic template decomposition, precursor decomposition, and crystal sintering occur simultaneously and rapidly, easily leading to pore collapse and particle agglomeration, resulting in a rapid decrease in specific surface area and a reduction in surface active sites. Furthermore, the control window for calcination parameters is narrow, leading to large fluctuations in product performance. The segmented calcination process of this invention first slowly removes the organic template at a low temperature, fully preserving the mesoporous structure left by the template, and then raises the temperature to a suitable level to complete precursor decomposition and crystallization. This ensures both product purity and crystallinity while maximizing the preservation of the hierarchical pore structure and surface activity defects, achieving a precise balance between pore structure preservation and crystal activity. Simultaneously, the segmented calcination process has a wider control window, better product performance stability, and is easier to scale up for industrial production, with smaller batch-to-batch performance differences.

[0027] 5. The raw materials used in this invention are all common industrial-grade chemical raw materials. The magnesium source is magnesium chloride hexahydrate, a bulk chemical product. The morphology regulator, soft template, and modifier are all commonly used chemical products. The raw materials are readily available and inexpensive, and there are no scarce or high-risk reagents. Compared with the preparation process using expensive organic template agents and special surfactants in the prior art, the raw material cost of this invention is significantly reduced. Moreover, the bio-based raw materials such as sucrose are environmentally friendly and easily degradable, leaving no toxic or harmful residues after calcination and decomposition, and will not generate hazardous waste. At the same time, the preparation process of this invention is simple, and the equipment used is all commonly used in the chemical industry, such as stirred reactors, hydrothermal reactors, filtration equipment, and tubular furnaces. No special equipment needs to be customized. Existing chemical plants and equipment can achieve large-scale production with simple adjustments. The process has strong adaptability, small scale-up effect, and good prospects for industrial promotion.

[0028] 6. The coral-like nano-magnesium oxide prepared by this invention possesses excellent structural and chemical stability, and can be regenerated and recycled after adsorption saturation through simple high-temperature calcination. Existing ordinary nano-magnesium oxide is difficult to regenerate after adsorption saturation; after multiple regenerations, the particles are prone to sintering and agglomeration, the pores are prone to collapse, and the adsorption performance decays rapidly, typically allowing only a few uses. Long-term use is costly, and waste adsorbent easily causes secondary pollution. The hierarchical coral-like structure of this invention has good structural rigidity, and the lanthanum-modified species have good thermal stability. After high-temperature calcination regeneration, the morphology and pore structure can be well maintained, and the active sites can be effectively restored. Even after multiple cycles, it can still maintain high adsorption performance. Excellent recycling performance can significantly reduce the operating costs of sugar juice purification and reduce the amount of waste adsorbent generated. At the same time, the adsorbent itself is sulfur-free and non-toxic, and can be safely disposed of after disposal, combining good economic and environmental benefits, and meeting the needs of long-term stable operation in the sugar industry. Attached Figure Description

[0029] Figure 1 The figure shows the effect of different concentrations of coral-like nano-MgO on the decolorization performance of sugar juice.

[0030] Figure 2 The graph shows the effect of different decolorization times on the decolorization performance of the sugar juice.

[0031] Figure 3 The graph shows the effect of different pH values ​​on the decolorization performance of sugar juice.

[0032] Figure 4 The graph shows the effect of different decolorization temperatures on the decolorization performance of sugar juice.

[0033] Figure 5 The image shows the X-ray diffraction (XRD) pattern of the coral-like nano-MgO prepared in Example 1.

[0034] Figure 6 The Fourier transform infrared (FTIR) spectrum of the coral-like nano-MgO prepared in Example 1 is shown.

[0035] Figure 7 The image shows a low-magnification SEM image of the coral-like nano-MgO prepared in Example 1.

[0036] Figure 8 The image shows a high-magnification SEM image of the coral-like nano-MgO prepared in Example 1. Detailed Implementation

[0037] The present invention will be further described in detail below with reference to specific embodiments and single-factor optimization experiments, but the scope of protection of the present invention is not limited to the content described.

[0038] In an embodiment of the present invention, a process for preparing coral-like nano-MgO includes the following steps:

[0039] (1) Preparation of precursor solution: Add magnesium chloride hexahydrate to a mixed solvent of ethylene glycol and deionized water and stir magnetically at room temperature until completely dissolved; add trisodium citrate dihydrate, sucrose, and lanthanum chloride hexahydrate in sequence and continue stirring until a homogeneous and transparent mixed salt solution is formed. The volume ratio of the ethylene glycol-deionized water mixed solvent is 3-5:1, the amount of trisodium citrate dihydrate is 3%-10% of the mass of magnesium chloride hexahydrate, the amount of sucrose is 5%-12% of the mass of magnesium chloride hexahydrate, and the amount of lanthanum chloride hexahydrate is 0.2%-1.2% of the molar ratio of lanthanum to magnesium.

[0040] (2) Coupled precipitation and solvothermal growth: Prepare a sodium carbonate-urea composite precipitant and add it dropwise to the mixed salt solution in step (1). After the addition is complete, continue to stir until uniform. Then transfer it to a hydrothermal reactor lined with polytetrafluoroethylene and seal it for solvothermal treatment. The molar ratio of sodium carbonate to urea in the composite precipitant is 0.5-1:1. The temperature of the solvothermal treatment is 120-160℃ and the holding time is 2-6h. The filling degree of the reactor is controlled at 65%-75%. The molar ratio of magnesium to carbonate in the system is 1.1-1.5:1.

[0041] (3) Post-treatment and drying: After the reaction is completed, the mixture is naturally cooled to room temperature, allowed to stand and age at room temperature, and then filtered to obtain a white precursor precipitate. The precipitate is washed alternately with deionized water and anhydrous ethanol until the filtrate is free of chloride ions. The washed precipitate is placed in an oven and dried at 78-82℃ for 9-10 h before being ground to obtain precursor powder.

[0042] (4) Segmented calcination crystallization: The precursor powder is spread evenly in a corundum boat and placed in a tube furnace. It is calcined in an air atmosphere using a two-stage temperature program. After natural cooling in the furnace, coral-like nano-MgO is obtained. The two-stage temperature program calcination is as follows: first, the temperature is increased to 250-300℃ at 1-3℃ / min and held for 1-2h, and then the temperature is increased to 420-480℃ at 2-4℃ / min and held for 1-3h.

[0043] Technical principle of the invention:

[0044] (a) The role of each raw material

[0045] 1. Magnesium chloride hexahydrate: The core magnesium source, providing magnesium for the product magnesium oxide. It is the basic raw material for crystal growth, and its amount is fixed to ensure the consistency of the reaction system.

[0046] 2. Ethylene glycol-deionized water mixed solvent: Ethylene glycol is a high-viscosity polar organic solvent that can reduce the diffusion rate of ions in the system, inhibit the agglomeration and growth between particles, and selectively adsorb onto specific crystal faces of the precursor to assist in one-dimensional directional crystal growth; Deionized water is used to adjust the polarity and viscosity of the system, ensure the full dissolution of various salt reagents, balance the reaction rate, and reduce the overall cost of raw materials.

[0047] 3. Trisodium citrate dihydrate: a chelating morphology regulator. Citrate ions can form stable chelates with free magnesium ions in the solution, reducing the concentration of free magnesium ions and slowing down the precipitation reaction rate. At the same time, citrate ions can preferentially adsorb on specific crystal faces of the precursor crystal, changing the growth energy barrier of different crystal faces, inducing the crystal to preferentially grow along the one-dimensional direction, and finally self-assemble to form a coral-like branched hierarchical structure.

[0048] 4. Sucrose: A bio-based soft template agent that is uniformly dispersed in the interparticle spaces and on the surface during the precursor precipitation and solvothermal reaction, without participating in the precipitation chemical reaction. During the subsequent calcination process, sucrose is gradually carbonized and decomposed, leaving abundant mesoporous channels inside and on the surface of magnesium oxide particles, constructing a hierarchical porous structure. At the same time, it can increase the hydroxyl content on the surface of magnesium oxide, providing more active sites for pigment adsorption.

[0049] 5. Anhydrous sodium carbonate: A fast-acting precipitant that can rapidly ionize and release carbonate ions, quickly forming a large number of uniform crystal nuclei in the early stages of the reaction, providing a growth substrate for the subsequent directional growth of crystals and ensuring the uniformity of product morphology.

[0050] 6. Urea: A homogeneous precipitant that slowly undergoes hydrolysis under solvothermal conditions, continuously and uniformly releasing carbonate and hydroxide ions. This allows crystals to grow slowly and uniformly on the basis of existing crystal nuclei, avoiding random agglomeration caused by excessively high local ion concentrations. At the same time, it can precisely control the precursor phase to be basic magnesium carbonate.

[0051] 7. Lanthanum chloride hexahydrate: a rare earth modifier. During calcination, a very small portion of trace lanthanum enters the magnesium oxide lattice to form a limited substitution solid solution, while the majority is enriched as highly dispersed lanthanum oxide species at the magnesium oxide grain boundaries and particle surfaces. The combined effect of these two factors induces lattice distortion, increases the surface coordination unsaturated sites and hydroxyl density, and the highly dispersed lanthanum oxide provides additional polar adsorption sites. Through hydrogen bonding and surface complexation, it significantly enhances the adsorption force and selectivity for polar pigments such as phenols and melanoidins in sugar juice.

[0052] (II) Synergistic Mechanism of Multiple Raw Materials

[0053] This invention is not a simple superposition of various technical means, but rather achieves a leapfrog improvement in performance through the synergistic coupling of multiple components and processes. The core synergistic mechanism is as follows:

[0054] 1. Synergistic Morphology Control: Trisodium citrate precisely controls the crystal growth rate through chelation, while ethylene glycol inhibits particle aggregation through viscosity. The synergistic effect of these two substances enables the directional assembly of one-dimensional crystals, forming a complete and regular coral-like branched structure. When trisodium citrate is used alone, crystal branches are prone to breakage, resulting in poor morphological regularity; when ethylene glycol is used alone, crystal growth directions are disordered, failing to form a clear coral-like hierarchical structure. The combination of the two substances simultaneously achieves growth direction control and aggregation inhibition, significantly improving morphological integrity and structural uniformity.

[0055] 2. Synergistic precipitation rate: Sodium carbonate is responsible for rapid nucleation, while urea is responsible for slow growth. The coupled precipitation system avoids the disordered morphology and uneven particle size caused by the excessively fast precipitation rate of sodium carbonate alone, and also solves the problems of insufficient nucleation quantity and excessively large particle size of urea alone. This results in uniform size, complete structure, and narrow particle size distribution of the coral-like branches.

[0056] 3. Structure-Pore Synergy: The coral-like hierarchical morphology constructs macroporous mass transfer channels between particles, while the calcined sucrose soft template forms mesoporous adsorption sites within the particles. The combination of these two elements forms a hierarchical pore structure of "macropore-mesopore". The hierarchical pores not only ensure the rapid diffusion and mass transfer of macromolecular pigments in the syrup, reducing adsorption resistance, but also provide sufficient internal surface adsorption sites, achieving a simultaneous improvement in mass transfer efficiency and adsorption capacity.

[0057] 4. Structure-Modification Synergy: The hierarchical porous structure provides a large specific surface area and abundant pores, fully exposing the surface activity defects generated by lanthanum modification and preventing the aggregation and deactivation of modified species; lanthanum modification, on the other hand, enhances the adsorption force per unit specific surface area and pigment selectivity. The combination of the two results in a performance improvement far exceeding the sum of the effects of single structural improvements and single modification improvements, producing a significant synergistic effect.

[0058] (III) Necessity and Importance of Selecting Key Process Parameters

[0059] 1. Solvothermal Temperature: The solvothermal temperature determines the hydrolysis rate and crystal growth rate of urea. At excessively low temperatures, the urea hydrolysis rate is extremely slow, resulting in incomplete precipitation and insufficient growth of the coral-like structure. At excessively high temperatures, the reaction rate is too fast, leading to excessive crystal growth and aggregation, damaging the morphology and causing a sharp decrease in specific surface area. A temperature range of 120-160℃ ensures that the urea hydrolysis rate matches the crystal growth rate, achieving controllable growth of a regular coral-like structure.

[0060] 2. Solvothermal time: The reaction time determines the degree of crystal growth and development. Too short a time results in insufficient crystal growth, short and few coral-like branches, and an incomplete hierarchical structure; too long a time leads to the Ostwald ripening effect, where small particles dissolve, large particles grow, the overall particle size increases, internal channels collapse, and the specific surface area decreases. A reaction time of 2-6 hours ensures complete hierarchical structure development while avoiding performance degradation due to over-ripening.

[0061] 3. Pre-calcination temperature: The core function of the pre-calcination stage is to slowly remove the organic template and achieve preliminary decomposition of the precursor. If the temperature is too low, the organic template will not decompose completely, and the residual carbon will clog the pores, reducing the effective specific surface area. If the temperature is too high, the template will decompose violently, and the rapid escape of a large amount of gas can easily lead to pore wall collapse. Simultaneously, premature and rapid decomposition of the precursor will damage the final morphology and structure. A temperature range of 250-300℃ allows for slow and controllable decomposition of the template, preserving the integrity of the pore structure to the greatest extent possible.

[0062] 4. Calcination Final Temperature: The final calcination temperature determines the degree of precursor decomposition and crystallinity. If the temperature is too low, the basic magnesium carbonate precursor decomposes incompletely, resulting in low product purity and insufficient active sites. If the temperature is too high, the crystals sinter and agglomerate, significantly reducing the specific surface area and surface activity defects. A temperature range of 420-480℃ ensures complete precursor decomposition while maintaining appropriate crystallinity, preserving abundant surface defects and pore structure.

[0063] 5. Segmented calcination heating rate: The slow heating rate can ensure uniform decomposition of organic template and stable decomposition of precursor, avoid pore structure collapse and particle agglomeration caused by rapid heating, and improve the uniformity of product morphology and pore structure.

[0064] (iv) Unexpected technical effects

[0065] This invention achieves a synergistic improvement in the structure and performance of nano-magnesium oxide through multi-raw material composite regulation and multi-process coupling optimization, yielding technical effects that are beyond the expectations of those skilled in the art: First, it achieves the simultaneous and controllable construction of coral-like morphology and hierarchical mesoporous structure, significantly increasing specific surface area and pore volume while maintaining morphological regularity, solving the industry-wide problems of insufficient pore structure control by a single morphology and chaotic pore-forming morphology by a single method; Second, it achieves deep synergy between structural optimization and rare earth modification, with performance improvement far exceeding the linear superposition of the two techniques, significantly enhancing the adsorption selectivity for polar pigments; Third, through a segmented calcination process, it achieves a precise balance between pore structure retention and crystal activity, significantly improving the structural stability and recyclability of the product, with performance degradation after multiple uses far lower than existing similar products. These effects are not something that those skilled in the art could reasonably expect based on existing technology, and represent significant technological advancements.

[0066] To make the present invention more fully disclosed, more specific embodiments are described below.

[0067] Example 1

[0068] A process for preparing coral-like nano-MgO includes the following steps:

[0069] 1. Weigh 20.32g of magnesium chloride hexahydrate, add 80mL of ethylene glycol-deionized water mixture (volume ratio 4:1), and stir magnetically at 300r / min at room temperature for 30min until completely dissolved.

[0070] 2. Add 1.0g of trisodium citrate dihydrate, 1.5g of sucrose, and 0.2g of lanthanum chloride hexahydrate (La / Mg molar ratio 0.57%) to the solution, and continue stirring for 20 minutes until homogeneous and transparent.

[0071] 3. Preparation of composite precipitant: Dissolve 3.18g of anhydrous sodium carbonate and 3.0g of urea in 30mL of deionized water and stir until homogeneous; the molar ratio of Mg to total potential carbonate in the system is 1.25:1, which conforms to the stoichiometric ratio of basic magnesium carbonate.

[0072] 4. Place the mixed salt solution on a magnetic stirrer and slowly add the composite precipitant dropwise at a rate of 1 mL / min. After the addition is complete, continue stirring for 10 min. Then transfer it to a 150 mL polytetrafluoroethylene-lined hydrothermal reactor and seal it. Control the filling degree to 73% and perform solvothermal treatment at 140℃ for 4 h.

[0073] 5. After naturally cooling to room temperature, allow to stand and age at room temperature for 3 hours, then filter to obtain a white precipitate; wash alternately with deionized water and anhydrous ethanol until the filtrate is free of Cl. - (Detected with 0.1 mol / L AgNO3).

[0074] The precursor was obtained by drying at 6.80℃ for 10h; the precursor was spread on a corundum ark and placed in a tube furnace under static air atmosphere, heated to 280℃ at 2℃ / min and held for 1.5h for template removal and pre-decomposition, then heated to 450℃ at 3℃ / min and held for 2h for calcination and crystallization, and then naturally cooled in the furnace to obtain coral-like nano-MgO.

[0075] Example 2

[0076] A process for preparing coral-like nano-MgO includes the following steps:

[0077] 1. Weigh 20.32g of magnesium chloride hexahydrate, add 80mL of ethylene glycol-deionized water mixture (volume ratio 4:1), and stir magnetically at 300r / min at room temperature for 30min until completely dissolved.

[0078] 2. Add 1.5g of trisodium citrate dihydrate, 2.0g of sucrose, and 0.15g of lanthanum chloride hexahydrate to the solution, and continue stirring for 20 minutes until homogeneous and transparent.

[0079] 3. Preparation of composite precipitant: Dissolve 3.18g of anhydrous sodium carbonate and 3.0g of urea in 30mL of deionized water and stir until homogeneous; the molar ratio of Mg to total potential carbonate in the system is 1.25:1, which conforms to the stoichiometric ratio of basic magnesium carbonate.

[0080] 4. Place the mixed salt solution on a magnetic stirrer and slowly add the composite precipitant dropwise at a rate of 1 mL / min. After the addition is complete, continue stirring for 10 min. Then transfer it to a 150 mL polytetrafluoroethylene-lined hydrothermal reactor and seal it. Control the filling degree to 72% and perform solvothermal treatment at 130℃ for 5 h.

[0081] 5. After naturally cooling to room temperature, allow to stand and age at room temperature for 3 hours, then filter to obtain a white precipitate; wash alternately with deionized water and anhydrous ethanol until the filtrate is free of Cl. - (Detected with 0.1 mol / L AgNO3).

[0082] The precursor was obtained by drying at 6.80℃ for 10h; the precursor was spread on a corundum ark and placed in a tube furnace under static air atmosphere, heated to 280℃ at 2℃ / min and held for 1.5h for template removal and pre-decomposition, then heated to 430℃ at 3℃ / min and held for 2.5h for calcination and crystallization, and then naturally cooled in the furnace to obtain coral-like nano-MgO.

[0083] Example 3

[0084] A process for preparing coral-like nano-MgO includes the following steps:

[0085] 1. Weigh 20.32g of magnesium chloride hexahydrate, add 80mL of ethylene glycol-deionized water mixture (volume ratio 4:1), and stir magnetically at 300r / min at room temperature for 30min until completely dissolved.

[0086] 2. Add 0.8g of trisodium citrate dihydrate, 1.2g of sucrose, and 0.25g of lanthanum chloride hexahydrate to the solution, and continue stirring for 20 minutes until homogeneous and transparent.

[0087] 3. Preparation of composite precipitant: Dissolve 3.18g of anhydrous sodium carbonate and 3.0g of urea in 30mL of deionized water and stir until homogeneous; the molar ratio of Mg to total potential carbonate in the system is 1.25:1, which conforms to the stoichiometric ratio of basic magnesium carbonate.

[0088] 4. Place the mixed salt solution on a magnetic stirrer and slowly add the composite precipitant dropwise at a rate of 1 mL / min. After the addition is complete, continue stirring for 10 min. Then transfer it to a 150 mL polytetrafluoroethylene-lined hydrothermal reactor and seal it. Control the filling degree to 73% and perform solvothermal treatment at 150℃ for 3 h.

[0089] 5. After naturally cooling to room temperature, allow to stand and age at room temperature for 3 hours, then filter to obtain a white precipitate; wash alternately with deionized water and anhydrous ethanol until the filtrate is free of Cl. - (Detected with 0.1 mol / L AgNO3).

[0090] The precursor was obtained by drying at 6.80℃ for 10h; the precursor was spread on a corundum ark and placed in a tube furnace under static air atmosphere, heated to 280℃ at 2℃ / min and held for 1.5h for template removal and pre-decomposition, then heated to 480℃ at 3℃ / min and held for 1.5h for calcination and crystallization, and then naturally cooled in the furnace to obtain coral-like nano-MgO.

[0091] (I) Single-factor optimization experiment for the preparation of coral-like nano-MgO

[0092] The preparation method is basically the same as in Example 1. Only one variable is changed in each group of experiments, while all other parameters are kept fixed to explore the optimal process parameters.

[0093] Performance testing methods:

[0094] Measure 50 mL of brown sugar reconstituted solution into a 250 mL Erlenmeyer flask and adjust the initial pH of the reaction system to 5.00. Then, add MgO to the sugar solution in a mass concentration gradient of 6 g / L. Place the mixture in a thermostatic magnetic stirrer and stir continuously at 60 °C for 40 min. After the reaction, allow it to settle at room temperature, then transfer it to a centrifuge and centrifuge at 6000 r / min for 6 min. Collect the centrifuged sugar solution and adjust its pH back to 7.00. Filter the solution through a microporous membrane to obtain the decolorized filtrate. Measure the refractive index B of the filtrate using an Abbe refractometer and its absorbance at 560 nm using a UV spectrophotometer. Calculate the decolorization rate of the sugar solution based on these measurements.

[0095] Experiment 1: Effect of the dosage of trisodium citrate dihydrate on product properties

[0096] Experimental plan:

[0097] The preparation method is basically the same as in Example 1, except that the amount of trisodium citrate dihydrate is changed. Five levels of trisodium citrate dihydrate were set: 0, 0.5g, 1.0g, 1.5g, and 2.0g. Coral-shaped nano-MgO samples were prepared, and the decolorization rate of the sugar juice was tested. The results are shown in the table below.

[0098] Experimental data:

[0099]

[0100] Conclusion Analysis:

[0101] When the dosage of trisodium citrate dihydrate is 0, the product lacks a distinct coral-like structure, consisting mainly of random particle aggregates, and the decolorization rate is low, indicating that the morphology control ability of the single ethylene glycol medium is limited. As the dosage increases from 0 to 1.0 g, the chelation and crystal face adsorption of citrate ions gradually become apparent, crystals preferentially grow along the one-dimensional direction, coral-like branches gradually develop fully, and the decolorization rate increases significantly. When the dosage exceeds 1.0 g, excessive citrate ions excessively inhibit the crystal growth rate, the branch structure becomes thinner and more prone to breakage, and internal channels collapse, leading to a simultaneous decrease in decolorization performance. In conclusion, the optimal dosage of trisodium citrate dihydrate is 1.0 g.

[0102] Experiment 2: Effect of sucrose dosage on product properties

[0103] Experimental plan:

[0104] The preparation method is basically the same as in Example 1, except that the amount of sucrose is changed. Five levels of sucrose were set: 0, 0.5g, 1.0g, 1.5g, and 2.0g. Coral-shaped nano-MgO samples were prepared, and the decolorization rate of the sugar juice was tested. The results are shown in the table below.

[0105] Experimental data:

[0106]

[0107] Conclusion Analysis:

[0108] Without added sucrose, the product exists only in the macropores between particles, with low mesopore content and limited internal adsorption sites, resulting in a low decolorization rate. As the amount of sucrose increases, the number of mesopores left from decomposition during calcination gradually increases, leading to an increase in the number of adsorption sites and a continuous rise in the decolorization rate. When the sucrose content exceeds 1.5g, the soft template content becomes too high, causing adjacent pores to collapse and merge during calcination, which in turn leads to a decline in adsorption performance. Therefore, the optimal amount of sucrose is 1.5g.

[0109] Experiment 3: Effect of Lanthanum Chloride Hexahydrate Dosage on Product Properties

[0110] Experimental plan:

[0111] The preparation method is basically the same as in Example 1. Using the mass of lanthanum chloride hexahydrate as a variable, five levels were set: 0, 0.1g, 0.2g, 0.3g, and 0.4g. Coral-shaped nano-MgO samples were prepared, and the decolorization rate of the sugar juice was tested. The results are shown in the table below.

[0112] Experimental data:

[0113]

[0114] Conclusion Analysis:

[0115] Without the addition of lanthanum modifier, the product decolorizes solely through physical adsorption and weak surface hydrogen bonding, resulting in weak adsorption of polar pigments and a low decolorization rate. The introduction of trace amounts of lanthanum can induce lattice distortion and highly dispersed active sites on the magnesium oxide surface, enhancing the adsorption force and selectivity for polar pigments. Therefore, the decolorization rate increases significantly with increasing lanthanum dosage. When the lanthanum dosage exceeds 0.2g, excess lanthanum species aggregate at grain boundaries and on particle surfaces, not only blocking some mesoporous channels but also causing excessive lattice distortion that disrupts crystal structure stability, ultimately leading to a simultaneous decrease in decolorization performance. In summary, the optimal dosage of lanthanum chloride hexahydrate is 0.2g.

[0116] Experiment 4: Effect of solvothermal temperature on product properties

[0117] Experimental plan:

[0118] The preparation method is basically the same as in Example 1, except that the solvothermal temperature is changed. Five levels of solvothermal temperature are set: 100℃, 120℃, 140℃, 160℃, and 180℃. Coral-shaped nano-MgO samples are prepared, and the decolorization rate of sugar juice is tested. The results are shown in the table below.

[0119] Experimental data:

[0120]

[0121] Conclusion Analysis:

[0122] At 100℃, the degree of urea hydrolysis is extremely low, the precipitation reaction is incomplete, and the coral-like structure does not grow sufficiently, resulting in poor product performance. As the temperature increases, the urea hydrolysis rate accelerates, crystal growth becomes more complete, the coral-like hierarchical structure develops more fully, and performance continuously improves. At 140℃, the urea hydrolysis rate and crystal growth rate are optimally matched, achieving the best product structure and performance. Above 160℃, the reaction rate becomes too fast, leading to excessive crystal growth and aggregation, morphological damage, sintering and collapse of the pores, and a sharp drop in decolorization performance. In summary, the optimal temperature for solvothermal treatment is 140℃.

[0123] Experiment 5: Effect of solvothermal time on product properties

[0124] Experimental plan:

[0125] The preparation method is basically the same as in Example 1, except that the heat preservation time is changed. Five levels of solvothermal preservation time are set: 1h, 2h, 4h, 6h, and 8h. Coral-shaped nano-MgO samples are prepared, and the decolorization rate of sugar juice is tested. The results are shown in the table below.

[0126] Experimental data:

[0127]

[0128] Conclusion Analysis:

[0129] When the reaction time is too short, crystal growth is insufficient, the coral-like branches are short and few in number, and the hierarchical structure is incomplete, resulting in low performance. As the reaction time increases, the crystals gradually grow and develop, the coral-like hierarchical structure becomes more complete, and the performance improves accordingly, reaching its optimal value at 4 hours. After the reaction time exceeds 4 hours, a significant Ostwald ripening effect occurs in the system; small particles gradually dissolve, large particles continue to grow, the overall particle size increases, and internal mesopores collapse and merge, leading to a decrease in specific surface area and reduced decolorization performance. In summary, the optimal holding time for solvothermal treatment is 4 hours.

[0130] Experiment 6: Effect of pre-calcination temperature on product properties

[0131] Experimental plan:

[0132] The preparation method is basically the same as in Example 1, except that the pre-calcination temperature is changed. Five levels of pre-calcination temperature are set: 200℃, 250℃, 280℃, 300℃, and 350℃. Coral-shaped nano-MgO samples are prepared, and the decolorization rate of sugar juice is tested. The results are shown in the table below.

[0133] Experimental data:

[0134]

[0135] Conclusion Analysis:

[0136] At 200℃, organic templates such as sucrose decompose incompletely, and the residual carbon can clog some mesoporous channels, resulting in a low effective specific surface area and limited decolorization performance. When the temperature rises to 280℃, the template decomposes and carbonizes slowly, preserving the most intact pore structure and achieving optimal decolorization performance. Above 300℃, the template decomposes too rapidly, causing a large amount of gas to escape violently in a short time, easily leading to pore wall collapse; simultaneously, the precursor decomposes prematurely and violently, damaging the final morphology and pore structure, resulting in decreased performance. In summary, the optimal pre-calcination temperature is 280℃.

[0137] Experiment 7: Effect of final calcination temperature on product properties

[0138] Experimental plan:

[0139] The preparation method is basically the same as in Example 1, except that the final calcination temperature is changed. Five levels of final calcination temperature are set: 380℃, 420℃, 450℃, 480℃, and 520℃. Coral-shaped nano-MgO samples are prepared, and the decolorization rate of sugar juice is tested. The results are shown in the table below.

[0140] Experimental data:

[0141]

[0142] Conclusion Analysis:

[0143] At 380℃, the basic magnesium carbonate precursor decomposes incompletely, leaving residual precursor phases in the product. This results in low purity and insufficient surface active sites, leading to poor decolorization performance. As the calcination temperature increases, precursor decomposition becomes more complete, and crystallinity gradually improves. At 450℃, the product purity, pore structure, and surface defects reach an optimal balance, resulting in the best performance. Above 480℃, significant sintering and agglomeration occur, with particle growth, pore shrinkage and collapse, a rapid decrease in specific surface area, and a substantial reduction in surface active sites, significantly decreasing decolorization performance. Therefore, the optimal final calcination temperature is 450℃.

[0144] Experiment 8: Effect of calcination holding time on product properties

[0145] Experimental plan:

[0146] The preparation method is basically the same as in Example 1, except that the calcination and holding time at 450℃ is changed. Five levels of calcination and holding time at 450℃ are set for 0.5h, 1h, 2h, 3h and 4h to prepare coral-like nano MgO samples. The decolorization rate of sugar juice is tested and the results are shown in the table below.

[0147] Experimental data:

[0148]

[0149] Conclusion Analysis:

[0150] When the holding time is too short, the precursor decomposes incompletely, resulting in insufficient crystallinity and suboptimal product purity and activity, thus leading to lower performance. At 2 hours of holding time, the precursor decomposes completely, the crystal form develops fully without significant sintering, and both structure and performance reach their optimal levels. Holding times exceeding 2 hours result in prolonged high-temperature environments causing continuous particle growth and gradual pore sintering, leading to a continuous decline in adsorption performance over time. Therefore, the optimal holding time for calcination is 2 hours.

[0151] (II) Single-factor optimization experiment for sugar juice purification

[0152] (1) Effect of mass concentration on decolorization rate

[0153] 50 mL of brown sugar reconstituted solution was transferred to a 250 mL Erlenmeyer flask, and the initial pH of the reaction system was adjusted to 5.00. Subsequently, coral-like nano-MgO prepared in Example 1 was added to the sugar solution at mass concentration gradients of 2, 4, 6, 8, and 10 g / L, respectively. The mixture was placed in a constant-temperature magnetic stirrer and stirred continuously at 30 °C for 30 min. After the reaction was completed, the mixture was allowed to settle at room temperature and then transferred to a centrifuge and centrifuged at 6000 r / min for 6 min. The centrifuged sugar solution was collected, and its pH was adjusted back to 7.00. After filtration through a microporous membrane, a decolorized filtrate was obtained. The refractive index B of the filtrate was measured using an Abbe refractometer, and its absorbance was measured at a wavelength of 560 nm using a UV spectrophotometer. Based on these measurements, the color value and decolorization rate of the sugar solution were calculated.

[0154] (2) Effect of adsorption time on decolorization rate

[0155] The pH of the brown sugar reconstitution solution to be treated was set to 5.00 using a pH meter. Coral-shaped nano-MgO prepared in Example 1 was added to five containers containing 50 mL of the above sugar solution at a uniform concentration of 6 g / L. A magnetic stirrer was started at a constant temperature of 30 °C, and the stirring reaction time was set to 30, 40, 50, 60, and 70 min, respectively. After the adsorption reaction was completed, each sugar solution was centrifuged at 6000 r / min for 6 min. The centrifuged sugar solution was collected, and its pH was adjusted back to 7.00. The decolorized filtrate was obtained after filtration through a microporous membrane. The refractive index B of the filtrate was measured using an Abbe refractometer, and its absorbance was measured at a wavelength of 560 nm using a UV spectrophotometer. Based on these measurements, the color value and decolorization rate of the sugar solution were calculated.

[0156] (3) Effect of initial pH value of the system on decolorization rate

[0157] 50 mL of brown sugar reconstituted solution was accurately measured and placed in five beakers. The initial pH of each group of sugar solutions was adjusted sequentially to 5.00, 6.00, 7.00, 8.00, and 9.00 using a pH meter. Subsequently, coral-like nano-MgO prepared in Example 1 was added to each group at a uniform mass concentration of 6 g / L. The mixtures were placed in a constant-temperature magnetic stirrer, and the reaction temperature was controlled at 30 °C for continuous stirring and adsorption for 40 min. After the reaction was completed, the mixture was allowed to stand at room temperature and then centrifuged at 6000 r / min for 6 min. The centrifuged sugar solution was collected, and its pH was adjusted back to 7.00. After filtration through a microporous membrane, the decolorized filtrate was obtained. The refractive index B of the filtrate was measured using an Abbe refractometer, and its absorbance was measured at a wavelength of 560 nm using a UV spectrophotometer. The color value and decolorization rate of the sugar solution were calculated based on these measurements.

[0158] (4) Effect of adsorption temperature on decolorization rate

[0159] The pH of the brown sugar reconstitution solution to be treated was adjusted to 5.00 beforehand. 50 mL of this solution was pipetted into five beakers, and coral-like nano-MgO prepared in Example 1 was added to each beaker at a concentration of 6 g / L. The beakers were then placed in constant-temperature magnetic stirrers at 30, 40, 50, 60, and 70 °C for 40 min of constant-temperature stirring and adsorption. After the reaction, the system was allowed to cool naturally to room temperature and then centrifuged at 6000 r / min for 6 min. The centrifuged solution was collected, and its pH was adjusted back to 7.00. The solution was then filtered through a microporous membrane to obtain a decolorized filtrate. The refractive index B of the filtrate was measured using an Abbe refractometer, and its absorbance was measured at 560 nm using a UV spectrophotometer. Based on these measurements, the color value and decolorization rate of the sugar solution were calculated.

[0160] Analysis of the cleaning properties of sugar juice:

[0161] (1) Effect of the mass concentration of coral-like nano-MgO on the decolorization performance of sugar juice

[0162] Test results are available Figure 1 ,Depend on Figure 1 It can be seen that as the mass concentration of coral-like nano-MgO increases from 2 g / L to 10 g / L, the decolorization rate shows a continuous upward trend. The decolorization rate increases significantly in the 2-6 g / L range, but the rate of increase slows down noticeably after the mass concentration exceeds 6 g / L. Under low dosage conditions, the system provides limited effective adsorption sites. Increasing the dosage of coral-like nano-MgO can significantly increase the number of active adsorption sites and promote the adsorption and removal of colored substances. When the mass concentration of coral-like nano-MgO is higher than 6 g / L, the concentration of remaining colored substances in the liquid phase decreases significantly, and further increasing the dosage of coral-like nano-MgO has limited effect on improving decolorization performance. Considering both the decolorization effect and the cost of raw materials, the optimal mass concentration of coral-like nano-MgO for this system is 6 g / L.

[0163] (2) Effect of decolorization time on the decolorization performance of sugar juice

[0164] Test results are available Figure 2 ,Depend on Figure 2 It can be seen that the coral-like nano-MgO exhibits a higher decolorization rate and a faster adsorption rate under various time conditions, reflecting its advantages in terms of pore structure characteristics and accessibility of surface active sites, which is conducive to improving mass transfer and adsorption efficiency. When the adsorption time exceeds 40 min, the increase in decolorization rate decreases significantly, and the system gradually approaches the equilibrium state. Further extending the time has limited effect on improving the decolorization effect. Therefore, the optimal decolorization time is 40 min.

[0165] (3) Effect of pH value on decolorization rate

[0166] Test results are available Figure 3 ,Depend on Figure 3 It can be seen that the coral-like nano MgO also shows a fluctuating trend with increasing pH, but the fluctuation range is small. The decolorization efficiency is maintained between 94.6% and 96.3% in the pH range of 5-9, with good stability and less affected by pH. The decolorization rate is the highest at pH=6, reaching 96.3%.

[0167] (4) Effect of decolorization temperature on the decolorization performance of sugar juice

[0168] Test results are available Figure 4 ,Depend on Figure 4 It can be seen that the decolorization rate of coral-like nano-MgO continuously increases with increasing temperature within the range of 30-60 °C, reaching a relatively high level near 60 °C, and then slightly decreases with further increases in temperature, showing relatively little influence from temperature fluctuations. This may be due to the presence of some residual magnesium hydroxide components in the coral-like nano-MgO, which enables it to form a more stable interaction with pigment molecules, thereby maintaining high adsorption performance over a wide temperature range. In summary, the optimal operating temperature for coral-like nano-MgO is 60 °C.

[0169] (III) Characterization results of coral-like nano-MgO

[0170] (1) X-ray diffractometer (XRD)

[0171] Test results are available Figure 5 ,Depend on Figure 5 It was found that the coral-like nano-MgO prepared in Example 1 exhibited diffraction peaks of magnesium hydroxide at 2θ = 18°, 33°, 38°, 50°, 58°, 62°, and 68°, respectively. MgO diffraction peaks were detected at 2θ = 36°, 42°, 62°, 74°, and 78°. The diffraction peaks of both the Mg(OH)₂ and MgO phases in the coral-like nano-MgO sample showed a significant decrease in intensity and a marked rightward shift (increased 2θ) relative to the standard reference rod. This reveals the profound influence of the preparation process of coral-like nano-MgO on crystal structure, defect density, and phase purity. The absolute intensities of both the Mg(OH)₂ and MgO main peaks in the coral-like nano-MgO were lower than expected by the pure phase standard, indicating a decrease in crystallinity and a reduction in grain size. According to Bragg's equation: nλ = 2dsinθ, when the diffraction angle θ increases (peak position shifts to the right), the interplanar spacing d must decrease. The rightward shift of the peak position directly indicates that the lattice of the MgO phase has shrunk. The rightward shift of the MgO peak in coral-like nano-MgO is mainly due to the micro-strain or structural defects of the sample itself, rather than instrument error.

[0172] (2) FTIR (Full-Time Infrared Spectroscopy)

[0173] Test results are available Figure 6 ,Depend on Figure 6 It can be seen that the coral-like nano-MgO surface prepared in Example 1 is simultaneously at 2338 cm⁻¹ - ¹The presence of a trace absorption peak originates from the antisymmetric stretching vibration of atmospheric CO2. This is due to carbonate species formed by the adsorption of atmospheric CO2. This is closely related to the high adsorption performance and high specific surface area of ​​coral-like nano-MgO, a common surface modification phenomenon after exposure to the environment. It also confirms that the precursor was essentially completely decomposed at 450 °C, leaving only trace amounts of surface carbonate. The coral-like nano-MgO exhibits a peak at approximately 850-860 cm⁻¹. -1 The intermediate absorption at this point corresponds to the out-of-plane bending vibration of the carbonate ion, while the lower absorption occurs at approximately 650–450 cm⁻¹. -1 The absorption band in this region is attributed to the Mg-O lattice stretching vibration. This low wavenumber band directly confirms the formation of the target product, the MgO phase, and no ethylene glycol-related CH vibration peaks or Cl-related peaks were detected. - The relevant characteristic absorption indicates that organic media and soluble impurities have been effectively removed.

[0174] (3) Scanning electron microscopy analysis

[0175] Test results are available Figure 7 , 8 ,Depend on Figure 7 As can be seen, the coral-like nano-MgO prepared in Example 1 appears as numerous irregular micron-sized aggregates in the low-magnification SEM image (B). The particles are clearly aggregated on the substrate, exhibiting poor dispersibility. The aggregates have a wide size distribution, concentrated in the range of 5-15 μm, and are generally irregularly blocky with irregular edges and blurred interfaces. Figure 8 As can be seen from the high-magnification image (b), its surface is composed of a large number of disordered stacked nanounits, exhibiting significant wrinkles, curls, and layered textures. These structures intertwine to form a loose three-dimensional network, constructing a rich macroporous-mesoporous composite pore system, giving the material high porosity and surface roughness. This disordered porous structure indicates that the crystal growth process is restricted, and the nanounits are randomly attached and partially fused, resulting in low crystallinity and certain defects on the surface, consistent with the results of reduced peak intensity and peak position shift in XRD. Coral-like nano-MgO, on the other hand, is a disordered porous network composed of randomly stacked nanoparticles, with a high degree of aggregation and a loose structure. The low crystallinity and disordered structure of coral-like MgO may weaken its mechanical stability and dispersibility to some extent, but its abundant pores and defects help to provide more active sites and enhance the adsorption reaction activity.

[0176] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A preparation process for coral-like nano-MgO, characterized in that, Includes the following steps: (1) Preparation of precursor solution: Add magnesium chloride hexahydrate to ethylene glycol-deionized water mixed solvent and stir magnetically at room temperature until completely dissolved; add trisodium citrate dihydrate, sucrose and lanthanum chloride hexahydrate in sequence and continue stirring until a homogeneous and transparent mixed salt solution is formed. (2) Coupled precipitation and solvothermal growth: Prepare sodium carbonate-urea composite precipitant, add it dropwise to the mixed salt solution in step (1), and continue to stir evenly after the addition is complete; then transfer it to a hydrothermal reactor lined with polytetrafluoroethylene and seal it for solvothermal treatment; (3) Post-treatment and drying: After the reaction is completed, the mixture is naturally cooled to room temperature, allowed to stand and age at room temperature, and then filtered to obtain a white precursor precipitate. The precipitate is washed alternately with deionized water and anhydrous ethanol until the filtrate is free of chloride ions. The washed precipitate is placed in an oven and dried at 78-82℃ for 9-10 h before being ground to obtain precursor powder. (4) Segmented calcination crystallization: The precursor powder is spread evenly in the corundum boat, placed in a tube furnace, and calcined in an air atmosphere using a two-stage temperature rise program. After natural cooling in the furnace, coral-like nano-MgO is obtained.

2. The preparation process of coral-like nano-MgO according to claim 1, characterized in that, The volume ratio of the ethylene glycol-deionized water mixed solvent in step (1) is 3-5:

1.

3. The preparation process of coral-like nano-MgO according to claim 1, characterized in that, The amount of trisodium citrate dihydrate used in step (1) is 3%-10% of the mass of magnesium chloride hexahydrate, and the amount of sucrose used is 5%-12% of the mass of magnesium chloride hexahydrate.

4. The preparation process of coral-like nano-MgO according to claim 1, characterized in that, The amount of lanthanum chloride hexahydrate used in step (1) is 0.2%-1.2% molar ratio of lanthanum to magnesium.

5. The preparation process of coral-like nano-MgO according to claim 1, characterized in that, In step (2), the molar ratio of sodium carbonate to urea in the composite precipitant is 0.5-1:1, the molar ratio of magnesium to carbonate in the system is 1.1-1.5:1, the temperature of the solvent heat treatment is 120-160℃, the holding time is 2-6h, and the filling degree of the reactor is controlled at 65%-75%.

6. The preparation process of coral-like nano-MgO according to claim 1, characterized in that, In step (3), the washed precipitate is placed in an oven and dried at 78-82℃ for 9-10 h before being ground to obtain precursor powder.

7. The preparation process of coral-like nano-MgO according to claim 1, characterized in that, The two-stage temperature-raising calcination process in step (4) is as follows: first, raise the temperature to 250-300℃ at 1-3℃ / min and hold for 1-2 hours, then raise the temperature to 420-480℃ at 2-4℃ / min and hold for 1-3 hours.

8. A coral-like nano-MgO prepared according to any one of claims 1-7, characterized in that, The coral-like nano-MgO is assembled from nanorods to form a coral-like branched hierarchical structure with mesoporous hierarchical channels inside.

9. The application of the coral-like nano-MgO according to claim 8 in the purification and decolorization of sugar juice.

10. The application of the coral-like nano-MgO according to claim 9 in the purification and decolorization of sugar juice, characterized in that, The coral-like nano-MgO was added to the sugar juice to be purified at a pH of 5-9 at a mass concentration of 4-10 g / L. The adsorption and decolorization were carried out under constant temperature stirring at 30-70℃ for 20-60 min. After the adsorption was completed, the purified sugar juice was obtained by solid-liquid separation.

Citation Information

Patent Citations

  • Method for cleaning sugar juice by using newborn magnesium hydroxide

    CN122060937A